3D tomographic reconstruction of Spray G after multiple light scattering suppression using Fourier filtering - Lehnert, Bastian; Stiti, Mehdi; Wensing, Michael; Berrocal, Edouard (Liquid Atomization and Spray Systems Europe 2023, 2023)

Analysis of liquid spray structures using two-photon fluorescence laser sheet imaging - Ulrich, Hannah; Lehnert, Bastian; Guenot, Diego; Svendsen, Kristoffer; Lundh, Olle; Will, Stefan; Wensing, Michael; Berrocal, Edouard; Zigan, Lars (Vol 1 No 1 (2021): ICLASS Edinburgh 2021, 2021)
In this work two-photon laser-induced fluorescence (2p-LIF) laser sheet imaging is used to analyze the structure and the atomization behavior of water and ethanol sprays. Multiple light scattering is reduced by 2p-LIF measurements using a femtosecond laser. This allows high-contrast spray imaging close to the nozzle resulting in an improved identification of single liquid structures. A commercial 6-hole DISI (Direct-Injection Spark-Ignition) injector was studied at different injection pressures, operated with ethanol and water containing a LIF dye (fluorescein). Compared to water, the ethanol spray structure shows increased cone angles in the nozzle near-filed. For the size of the liquid structures, no clear dependency on the fluid properties is observed in this spray region.<br
Keywords: 2p-LIF; Spray; Atomization; Femtosecond

Distribution of Liquid Mass in Transient Sprays Measured Using Laser-Plasma-Driven X-Ray Tomography - Guenot, Diego; Svendsen, Kristoffer; Lehnert, Bastian; Ulrich, Hannah; Persson, Anders; Permogorov, Alexander; Zigan, Lars; Wensing, Michael; Lundh, Olle; Berrocal, Edouard (Physical Review Applied, 2022)
We report, the use of laser-plasma-driven x rays to reveal the three-dimensional (3D) structure of a highly atomizing water spray. Soft x rays approximately 5 keV are generated by means of a laser-plasma accelerator. Transmission radiography measurements are performed at different angles, by rotating a multihole injector. Using computer tomography, the local liquid volume distribution and its spatial variation are retrieved in 3D, showing up to 55% liquid fraction at the nozzle outlet, which decreases to below 7% within only 1 mm. The resolution of the liquid volume fraction is 0.5% while the spatial resolution of the radiographic images is 11.5μm. The x-ray source used here provides successful measurements of liquid mass distribution over a relatively large volume and is very promising for the analysis of a variety of challenging transient spray systems, e.g., the injection of liquid synthetic and biofuels used for future clean-combustion applications.
CRIS-Team Scopus Importer:2022-07-22

Effects of liquid properties on atomization and spray characteristics studied by planar two-photon fluorescence - Ulrich, Hannah; Lehnert, Bastian; Guenot, Diego; Svendsen, Kristoffer; Lundh, Olle; Wensing, Michael; Berrocal, Edouard; Zigan, Lars (Physics of Fluids, 2022)
In this work, planar two-photon laser-induced fluorescence (2p-LIF) is applied for the first time to analyze the fluid dependent spray structure and atomization behavior of water and ethanol in a quantitative way. A commercial six-hole DISI (Direct-Injection Spark-Ignition) injector was studied at different injection pressures, operated with liquids containing the LIF dye fluorescein. Specifically for DISI-injectors, the fluid-dependent atomization is very complex and not fully understood due to the cavitating, turbulent nozzle flow that dominates the spray formation. Optical access and analysis of the near-nozzle spray are often challenging due to multiple light scattering in dense regions which is reduced by 2p-LIF measurements using a femtosecond laser. This allows high-contrast spray imaging close to the nozzle, resulting in an improved identification of single liquid structures of the spray. Thus, a higher accuracy of sizing is possible. Compared to water, the ethanol spray shape shows increased cone angles in the nozzle near-field of about 6%, which cannot be explained by classical atomization theory based on aerodynamic breakup. The larger cone angle of ethanol was attributed to its larger viscosity, which could decelerate the flow at the wall of the injection hole, affecting the velocity profile of the emerging jet. The atomization shows a main jet breakup distance of 7-10 mm in which the structure sizes decreased drastically, specifically for water. For the size of the liquid structures in the near-nozzle region, which show dimensions of about 80-130 μm, ethanol exhibited about 2% smaller Feret's diameters than water for the tested time steps at 20 MPa. This effect is even more distinct for other injection pressures and positions at a further distance to the injector. For all investigated conditions and measurement positions downstream of the nozzle, ethanol showed on average about 24% smaller structures compared to the water spray. Although this trend is in accordance with the classical atomization theory based on the aerodynamic breakup mechanism, other effects, such as cavitation and nozzle-flow induced breakup, contribute to this behavior..
CRIS-Team Scopus Importer:2022-08-19

Experimental Study of High-Pressure Reacting and Non-reacting Sprays for Various Gasoline Blends - , Ankith Ullal; Lehnert, Bastian; Zhu, Shengrong; Révidat, Stephan; Shirley, Mark; Pyo Ha, Kyoung; Wensing, Michael; Ullrich, Johannes (SAE International Journal of Fuels and Lubricants, 2023)
Research into efficient internal combustion (IC) engines need to continue as the majority of vehicles will still be powered by IC or hybrid powertrains in the foreseeable future. Recently, lean-burn gasoline compression ignition (GCI) with high-pressure direct injection has been receiving considerable attention among the research community due to its ability to improve thermal efficiency and reduce emissions. To maximize GCI benefits in engine efficiency and emissions tradeoff, co-optimization of the combustion system and fuel formation is required. Thus, it is essential to study the spray characteristics of different fuels under engine-like operating conditions. In this work, high-pressure spray characteristics are experimentally studied for three blends of gasoline, namely, Naphtha, E30, and research octane number (RON) 98. A single-hole custom-built injector was used to inject fuel into a constant volume chamber with injection pressure varying from 40 MPa to 100 MPa. The chamber pressure was varied from 4 MPa to 7 MPa. The spray parameters measured were liquid and vapor penetration, liquid and vapor spray plume angle, and spray and flame luminosity area for reacting and non-reacting sprays. The measurement techniques used were shadowgraphy, Schlieren method, and flame luminosity area measurement. Liquid penetration followed the fuel density pattern and was shortest for Naphtha, followed by RON 98 and E30. The increase in injection pressure did not significantly affect liquid penetration, but improved atomization as well as reduced soot intensity. In addition, vapor penetration was increased on account of higher injection velocity and vaporized mass. The higher chamber pressure drastically reduced liquid and vapor penetration on account of increased drag. Compared to non-reacting sprays, vapor penetration and spray plume angle for reacting sprays deviated according to the fuel type. Ignition of the fuel increased vapor penetration and spray plume angle due to the expansion of hot gases. Naphtha ignited the earliest on account of its low RON and high volatility. It had the highest deviation from the corresponding non-reacting case for vapor penetration. RON 98 fuel only showed a slight increase in vapor plume angle indicating the start of reaction, whereas E30 did not show any deviation.<br
Keywords: Internal combustion engines; Engine efficiency; Lean burn engines; Gasoline; Combustion and combustion processes; Fuel injection

GDI Sprays with up to 200 MPa Fuel Pressure and Comparison of Diesel-like and Gasoline-Like Injector Designs - Lehnert, Bastian; Conrad, Chris; Wensing, Michael (SAE Technical Papers, 2020)
To address stricter emission limits, GDI develops to increased fuel pressure. Current gasoline injectors are already operating at a pressure of up to 35 MPa and an elevation is still promising lower particle emissions and increased efficiency. There have been only few studies of GDI sprays at pressures >50 MPa published. Contrary, in diesel engines injection pressure up to 250 MPa are common. GDI and diesel injector designs limit liquid penetration in different ways to avoid wall wetting, which has a negative impact on emissions in GDI combustion concepts. With elevated fuel pressure the question arises which design concept limits the penetration depth more effectively. To investigate the properties of high pressure sprays, a GDI injector (100 MPa max. fuel pressure) and an injector with diesel-like design are compared. High speed Shadowgraphy and Schlieren technique are used to gather information of liquid and vapor phase propagation. With Phase-Doppler-Anemometry (PDA) the diameter and the velocity of droplets in the sprays are recorded. Measurements are executed in a spray bomb with ambient pressure up to 4 MPa and ambient temperature up to 660 K. Results show that, increased fuel pressure lowers the mean and maximum diameter of the droplets. At the same time, considering ambient conditions, the spray penetration is not always higher at higher pressures, despite higher spray velocities. The injector design affects the penetration depth and the transition to the vapor phase, due to different rates of air entrainment. At higher fuel pressures the diesel design leads to faster vaporization, therefore the mixture formation and phase change are also faster, especially in high temperature ambient conditions. While a typical GDI design limits penetration more efficiently at moderate injection pressures and in low to moderate ambient conditions, the situation changes for very high injection pressure >50 MPa and late injection timing.
CRIS-Team Scopus Importer:2020-10-30

Long-Term Continuous Gas Diagnostics For Fuel Cell Systems: Development Of An Automatized Raman Metrology - Rüppel, Bastian; Lehnert, Bastian; Weiß, Lukas; Wensing, Michael (21st International Symposium on Application of Laser and Imaging Techniques to Fluid Mechanics, 2024)
Knowledge of the composition of gas flows in fuel cell systems is crucial for their understanding. In current research, this data is rarely recorded inline and in real-time due to the lack of suitable metrology. Here, we present an optical gas sensor. Green light (532 nm) from a 450 mW laser excites Raman scattering. A spectrometer analyzes the scattered light and a Python software extracts gas composition data automatized and in real-time. We designed a measurement cell that allows optical inline access to gas flow systems and is easy to implement. Therefore, common signal enhancement methods with more complex setups can not be applied. Literature data on scattering cross sections does not offer a reliable basis for calibration what constitutes the need for a gas conditioning system that allows fast preparation of well defined mixtures. We used it to present two principles of calibration. First, calibration based on relative scattering cross sections is the more stable possibility, because it is still valid in cases where laser power and integration time are changed. However, in consequence the results for one species are not independent from the other species. A poor signal, e.g. following from a low mole fraction in a single component, will introduce uncertainty in all components. We avoid that problem through direct linear correlation of signal strength of one species to its partial pressure, which is the second calibration variant. In this case, there is an influence of laser power and integration time. The additional information on overall pressure can be used in model systems, where the presence of undetected components can be ruled out. We can compare that information to pressure measurements to do plausibility checks on the Raman results in real-time. We apply the sensor in fuel cell system research, where measurement intervals of one second yield results of sufficient precision. Increasing integration time can further decrease the uncertainties where favorable. The measurement and data evaluation routines work stable and constant enough to monitor gas compositions in longterm operation. To date, the sensor can measure mixtures of nitrogen, oxygen, hydrogen and water vapor.<br
Keywords: Raman Sensor; Gas Diagnostics; Fuel Cell System; Scattering Cross Sections; Partial Pressure Calibration

Multiple scattering suppression for correct light transmission measurements through the ECN Spray G running with ethanol - Stiti, Mehdi; Lehnert, Bastian; Wensing, Michael; Berrocal, Edouard (31th Conference on Liquid Atomization and Spray Systems, 2022)

Planar droplet sizing for studying the influence of ethanol admixture on the spray structure of gasoline sprays - Kögl, Matthias; Mishra, Yogeshwar Nath; Baderschneider, Kevin; Conrad, Chris; Lehnert, Bastian; Will, Stefan; Zigan, Lars (Experiments in Fluids, 2020)
Abstract: A novel planar droplet sizing (PDS) technique based on laser-induced fluorescence (LIF) and Mie-scattering is utilized for the characterization of the spray structure under gasoline direct-injection spark-ignition (DISI) conditions. Fuel effects on the spray structure and cyclic variations are studied for a gasoline surrogate fuel (Toliso, consisting of 65 vol.% isooctane and 35 vol.% toluene) and the gasoline-ethanol blend E20 (20 vol.% ethanol admixture). Sauter mean diameter (SMD) results are compared with those from phase-Doppler anemometry (PDA) measurements showing good agreement especially at early points in time (up to 1.2 ms after start of injection). The liquid spray propagation and SMD are very similar for both fuels indicating similar atomization behavior. Both investigated fuels show comparable cyclic variations of the spray shape. A larger width and slightly larger droplet sizes are observed for the E20 spray when stronger evaporation occurs (at 2 ms). At these later points in time, the PDS-measured droplet sizes differ from the PDA-results. Here the limitation of the PDS-technique becomes obvious as a partial evaporation of the droplets may lead to large systematic errors. A numerical simulation of single droplets is provided for clarification of issues of droplet evaporation in PDS. Graphic abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2020-09-18

Quantifying extinction imaging of fuel sprays considering scattering errors - Lehnert, Bastian; Weiß, Lukas; Berrocal, Edouard; Wensing, Michael (International Journal of Engine Research, 2023)
In this work, we use the measurement technique of high-speed Diffuse Back Illumination Extinction Imaging (DBI-EI) to obtain quantitative information in the form of projected liquid volume (PLV) in a highly transient GDI process. For the DBI-EI setup we use a LED-Panel as the light source, which fulfills diffuse back illumination extinction imaging criteria. Measurements were carried out in a constant volume chamber, allowing easy optical access, and enabling measurements at real world ambient engine conditions. For the experiments, we use an Engine Combustion Network (ECN) Spray G injector and measure the sprays at ECN conditions. Moreover, we mount the injector in a motorized rotational system, enabling measurements of the sprays at precisely defined angles of observation. The DBI-EI technique requires a light source radiating uniformly in a certain range of an angle. Because of the diffuse radiation, an error in the quantification of the liquid phase results from the detection of multiple and forward scattered photons. This leads to an underestimation of the optical depth ((Formula presented.)), which further results in a false calculation of the projected liquid volume. Therefore, we must assume that DBI-EI results are wrong. To enable the use of DBI-EI in all spray regions independent of the measurement setup, we present a simulation-based method, which is correcting the (Formula presented.) for scattering effects. Results show, that the measured (Formula presented.) of the experimental setup, which we used in this work, is underestimated by at least a factor of 2.2. This factor increases with increasing spray densities. We can use the corresponding corrected PLV data to reconstruct three-dimensional data of the liquid volume fraction with the tomographic method filtered back projection. Thus, we obtain time and spatial resolved quantitative spray information, with an approach to correct undesired scattering effects, while keeping the experimental effort low.
CRIS-Team Scopus Importer:2023-04-28
Keywords: DBI-EI; multi scattering; Spray G; spray quantification

The 10th International Conference on Modeling and Diagnostics for Advanced Engine Systems - Lehnert, Bastian; Weiß, Lukas; Berrocal, Edouard; Wensing, Michael (COMODIA2022, 2022)

Tomographic reconstruction of spray evolution considering multiple light scattering effects - Lehnert, Bastian; Weiß, Lukas; Berrocal, Edouard; Wensing, Michael (The 10th International Conference on Modeling and Diagnostics for Advanced Engine Systems (COMODIA 2022), 2022)
Meeting stricter legal emission limits and the simultaneous introduction of new synthetic fuels are key challenges for current and future research in the field of engine combustion. A deep knowledge of spray behavior is mandatory to address these problems, as air‐fuel mixture and spray propagation in gasoline direct injection (GDI) are essential processes to achieve a highly efficient and clean combustion. Thus, a lot of effort is put into the identification of air‐fuel spray distributions. Most of them use lasers or X‐ray sources, which are accompanied by a high experimental complexity and further drawbacks. In this work, the measurement technique application of high speed diffuse back illumination extinction imaging (DBIEI) is used to obtain quantitative information in the form of projected liquid volume fraction (PLV). The DBIEI setup is simplified to enable an easier and quicker application for different experimental environments, using a LED-Panel as light source, which fulfills diffuse back illumination (DBI) criteria. Measurements are done in a constant volume chamber, allowing easy optical access with up to 200 mm in diameter and enabling measurements at real world ambient engine conditions. An engine combustion network (ECN) Spray G injector is used. ECN ambient conditions G1 (3.5 kg/m³ ambient density at 300°C), G2 (0.5 kg/m³ ambient density at 60°C) and G3 (1.01 kg/m³ ambient density at 60°C) are chosen. Isooctane is used as fuel. The injector is mounted in a motorized rotational system, enabling measurements of the spray at defined and exact angles. The DBIEI measurement technique suppresses the effect of beam steering at elevated ambient conditions, allowing the measurement of scattering based light attenuation by spray droplets. This requires a light source radiating uniformly over a certain angle‐range. Nevertheless, an inherent error in the quantification of liquid phase results from the detection of multiple scattered photons. The error is even more enhanced when using a non‐collimated light source. This leads to an underestimation of the optical depth (OD), which further results in a false calculation of the projected liquid volume. Therefore, beside very low‐density regions e.g. at spray boundaries, PLV results have to be assumed wrong. To enable the use of DBIEI in more dense spray regions, we present a simulation-based method correcting the ODs. Derived from this the corrected values indicate an underestimation of the OD of a factor greater than 2. The corresponding PLV data at different viewing angles is then used to reconstruct three-dimensional data of the liquid volume fraction (LVF) with filtered back projection (FBP). Thereby we can obtain time and spatial resolved quantitative spray information using an easy experimental setup, with an approach to correct beam steering and multiple scattering, while the experimental effort is kept low by using LED light sources. This data can be used for comparison, calibration and evaluation of simulation data of transient sprays, leading to detailed knowledge of spray behavior and mixture formation in different condition
Keywords: Tomography; Time resolved; DBIEI; Multi Scattering; Spray G

Tomographic reconstruction of spray evolution considering multiple light scattering effects: Characterization of an ECN Spray G Injector - Lehnert, Bastian; Weiß, Lukas; Berrocal, Edouard; Wensing, Michael (COMODIA 2022 - 10th International Conference on Modeling and Diagnostics for Advanced Engine Systems, 2022)
Meeting stricter legal emission limits and the simultaneous introduction of new synthetic fuels are key challenges for current and future research in the field of engine combustion. A deep knowledge of spray behavior is mandatory to address these problems, as air‐fuel mixture and spray propagation in gasoline direct injection (GDI) are essential processes to achieve a highly efficient and clean combustion. Thus, a lot of effort is put into the identification of air‐fuel spray distributions. Most of them use lasers or X‐ray sources, which are accompanied by a high experimental complexity and further drawbacks. In this work, the measurement technique application of high speed diffuse back illumination extinction imaging (DBIEI) is used to obtain quantitative information in the form of projected liquid volume fraction (PLV). The DBIEI setup is simplified to enable an easier and quicker application for different experimental environments, using a LED-Panel as light source, which fulfills diffuse back illumination (DBI) criteria. Measurements are done in a constant volume chamber, allowing easy optical access with up to 200 mm in diameter and enabling measurements at real world ambient engine conditions. An engine combustion network (ECN) Spray G injector is used. ECN ambient conditions G1 (3.5 kg/m3 ambient density at 300°C), G2 (0.5 kg/m3 ambient density at 60°C) and G3 (1.01 kg/m3 ambient density at 60°C) are chosen. Isooctane is used as fuel. The injector is mounted in a motorized rotational system, enabling measurements of the spray at defined and exact angles. The DBIEI measurement technique suppresses the effect of beam steering at elevated ambient conditions, allowing the measurement of scattering based light attenuation by spray droplets. This requires a light source radiating uniformly over a certain angle‐range. Nevertheless, an inherent error in the quantification of liquid phase results from the detection of multiple scattered photons. The error is even more enhanced when using a non‐collimated light source. This leads to an underestimation of the optical depth (OD), which further results in a false calculation of the projected liquid volume. Therefore, beside very low‐density regions e.g. at spray boundaries, PLV results have to be assumed wrong. To enable the use of DBIEI in more dense spray regions, we present a simulation-based method correcting the ODs. Derived from this the corrected values indicate an underestimation of the OD of a factor greater than 2. The corresponding PLV data at different viewing angles is then used to reconstruct three-dimensional data of the liquid volume fraction (LVF) with filtered back projection (FBP). Thereby we can obtain time and spatial resolved quantitative spray information using an easy experimental setup, with an approach to correct beam steering and multiple scattering, while the experimental effort is kept low by using LED light sources. This data can be used for comparison, calibration and evaluation of simulation data of transient sprays, leading to detailed knowledge of spray behavior and mixture formation in different conditions.
CRIS-Team Scopus Importer:2024-12-16
Keywords: DBIEI; Multi Scattering; Spray G; Time resolved; Tomography